2005
DOI: 10.1080/j.1440-1614.2005.01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Ole Taeao Afua, the New Morning: A Qualitative Investigation Into Samoan Perspectives on Mental Health and Culturally Appropriate Services

Abstract: The Fa'afaletui method is a new research method which is sensitive and responsive to Samoan cultural norms and is methodologically rigorous. Such an approach may be relevant for other Pacific Island cultures and other cultures, which have a strong emphasis on collectivity. The Samoan concept of self provides a theoretical foundation for understanding the mental health needs of Samoan people and a basis for developing appropriate services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
194
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(208 citation statements)
references
References 7 publications
5
194
0
Order By: Relevance
“…The FM and the First Interpreter indicated that more naturalistic tasks, such as ones related to cooking or attending church, would have been more appropriate. It has been suggested in the literature about Samoan culture (Anae, 2010;Sobralske, 2006;Tamasese, Peteru, Waldegrave, & Bush, 2005) that Western approaches may not always be suitable for individuals from this background. The incorporation of more meaningful and naturalistic activities into assessment may be more appropriate for all clients, irrespective of cultural background; however, the study highlights that this may be particularly important in relation to language assessment with the Samoan population.…”
Section: Discussionmentioning
confidence: 99%
“…The FM and the First Interpreter indicated that more naturalistic tasks, such as ones related to cooking or attending church, would have been more appropriate. It has been suggested in the literature about Samoan culture (Anae, 2010;Sobralske, 2006;Tamasese, Peteru, Waldegrave, & Bush, 2005) that Western approaches may not always be suitable for individuals from this background. The incorporation of more meaningful and naturalistic activities into assessment may be more appropriate for all clients, irrespective of cultural background; however, the study highlights that this may be particularly important in relation to language assessment with the Samoan population.…”
Section: Discussionmentioning
confidence: 99%
“…As affirmed through the work of Agnew, PulotuEndemann, Robinson, Suaalii-Sauni and Warren (2004) and Tamasese, Peteru, Waldegrave and Bush (2005), many Pacific people are relational beings legitimised by sacred relationships built on the values of tapu (sacred bonds), alofa (love and compassion), tautua (reciprocal service), fa'aloalo (respect and deference), fa'amaualalo (humility), and aiga (family); to them, culture is the core of their very existence, both individually and collectively. Nevertheless, being cognisant of the negative consequences of colonisation and forced acculturation among Pacific cultures is critical for working towards balanced intercultural relationships that can lead to positive outcomes for people of the Pacific.…”
Section: Commentsmentioning
confidence: 90%
“…Samoan people stop taking medication when they feel they have recovered (Tamasese et al . 1997; 2005). …”
Section: Mental Health Treatment For Samoan New Zealanders: Pacific Imentioning
confidence: 99%
“…1997; 2005). The elders felt that acculturation and socioeconomic stressors were the primary cause of mental illness in Samoan New Zealanders and that these factors were not given proper consideration in their treatment.…”
Section: Mental Health Treatment For Samoan New Zealanders: Pacific Imentioning
confidence: 99%
See 1 more Smart Citation